1990
DOI: 10.1901/jeab.1990.53-47
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence Classes Generated by Sequence Training

Abstract: In Experiment 1, 3, adult females were taught with verbal instructions and contingencies to select, in sequence, three arbitrary visual stimuli from an array of five stimuli. After four different sequences were taught, match-to-sample tests assessed emergent conditional relations among all stimuli that had been selected in the same order in the sequences. Subjects' performances indicated development of four stimulus classes, three based on ordinal position and one based on nonselection. Next, match-to-sample t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
58
0
10

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 15 publications
1
58
0
10
Order By: Relevance
“…For example, Sigurdardottir, Green, and Saunders (1990) tried to determine the role of instructions in stimulus-equivalence phenomena more directly, relying on small-group designs. They compared the effects of two 1Stimulus equivalence refers to a special stimulus class established by the training of at least two conditional discriminations (e.g., A-8 and 8-C) that results in four new conditional relations (8-A, C-8, A-C, and C-A), testifying to the symmetry, transitivity, and symmetric transitivity of the original two conditional discriminations, and called in aggregate stimulus equivalence (ct. Sidman & Tailby, 1982).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Sigurdardottir, Green, and Saunders (1990) tried to determine the role of instructions in stimulus-equivalence phenomena more directly, relying on small-group designs. They compared the effects of two 1Stimulus equivalence refers to a special stimulus class established by the training of at least two conditional discriminations (e.g., A-8 and 8-C) that results in four new conditional relations (8-A, C-8, A-C, and C-A), testifying to the symmetry, transitivity, and symmetric transitivity of the original two conditional discriminations, and called in aggregate stimulus equivalence (ct. Sidman & Tailby, 1982).…”
mentioning
confidence: 99%
“…21nstructional effects can be found not only in the explicit initial instructions to establish the conditional discriminations but can also be implicit in the pretraining task. For example, the derived ordinal classes in the Sigurdardottir et al (1990) study could have been facilitated by their pretraining task, which required ordering letters alphabetically. Lacking that pretraining, would their results have been similar to those of Lazar (1977)?…”
mentioning
confidence: 99%
“…Riegler and Baer (1989) have offered a developmental analysis and review of this and other literature on instructional control. Unfortunately, the literature on stimulus equivalence contains only a few studies in which instructions have been an independent variable (e.g., Sigurdardottir, Green, & Saunders, 1990).…”
mentioning
confidence: 99%
“…This position was not supported by subsequent demonstrations of equivalence class formation consisting of visual stimuli only such as arbitrary or abstract line drawings (Bush, Sidman, & De Rose, 1989;Hayes, Kohlenberg, & Hayes, 1991;Lazar, 1977;Saunders, Saunders, Kirby, & Spradlin, 1988;Sigurdardottir, Green, & Saunders, 1990;Spencer & Chase, 1996;Spradlin, Cotter, & Baxley, 1973;Wetherby, Karlan , & Spradlin, 1983;Wulfert, Greenway, & Dougher, 1994;Wulfert & Hayes, 1988) and nonsense syllables (Fields, Adams, Ve rh ave , & Newman, 1990;Fields, Newman, Adams, & Verhave, 1992;Fields, Reeve, Adams, & Verhave, 1991 ). These results also showed that equivalence classes can be formed from stimuli in only one sensory modality.…”
mentioning
confidence: 86%